Endogenous Protection in General Equilibrium: estimating political weights in the EU - Joseph Francis Francois; Douglas Nelson; Annette Pelkmans-Balaoing (Johannes Kepler University of Linz, Department of Economics, 2008)
We examine the political economy underpinnings of import protection in general equilibrium. Starting from a dual theoretical representation of production, trade, and consumption, we map a general representation of the real economy to underlying political processes aka the political support function to derive a general representation of the determinants of import protection. This includes the relatively standard approach of examining the pattern of tariffs in a Grossman-Helpman framework, as well as recent extensions linked to upstream and downstream linkages between sectors. Because we start from a relatively generic general equilibrium model of production, we have an immediate bridge between the theory and general equilibrium-based estimates of the welfare effects and rents generated by tariffs. We therefore follow the development of our generalized theoretical framework by introducing the use of general equilibrium estimates of the direct and indirect marginal impacts of protection at the sector level for econometric estimation of the revealed pattern of policy weights. This GE approach yields direct estimates of political weights based on economic effects, including cross-industry effects. The resulting weights lend insight into relative protection of agriculture and manufacturing. Working with data on the European union, we find that the strength of downstream linkages matters for policy weights and rates of protection, as does the national posture of industry. We also find support for a general political support function in the determination of tariffs, though results are mixed for the more narrow Grossman-Helpman specification. In the EU, nationality of industry seems to play a role in the setting of Community-wide import protection.
Keywords: F13; F14; D72; 330; political weights; political economy of import protection; Grossman-Helpman model; Protektionismus; Zolltarif; Agrarprotektionismus; Verarbeitendes Gewerbe; Mitgliedschaft; Macht; EU-Staaten